No-tillage Improves Winter Wheat (Triticum Aestivum L.) Grain Nitrogen Use Efficiency. Issue 19 (28th October 2019) - Omara, Peter; Aula, Lawrence; Oyebiyi, Fikayo; Nambi, Eva; Dhillon, Jagmandeep S.; Carpenter, Jonathan; Raun, William R
ABSTRACT: Tillage practices are among the factors that affect soil quality as well as use efficiency of fertilizer nitrogen (N). Data consisting of 24-site-years from two long-term experiments 222 (E222) located in Stillwater and 502 (E502) located in Lahoma, Oklahoma were used in this study. Treatments included pre-plant N rates of 0, 45, 90, and 135 kg N ha −1 at E222 and 0, 22.5, 45, 67, 90 and 112 kg N ha −1 at E502. The objective was to evaluate the influence of no-tillage (NT) on grain N uptake and N use efficiency (NUE) of winter wheat ( Triticum aestivum L.) relative to conventional tillage (CT). Generally, results indicated significantly higher grain N uptake and NUE under NT relative to CT. However, single-degree-of-freedom contrast at individual N rate indicated inconsistency in grain N uptake and NUE between experimental locations. Under both tillage practices, grain N uptake increased with N rate while NUE decreased as N rate increased. Overall, NUE and grain N uptake was 23% and 7.5% higher under NT compared to CT, respectively. Therefore, winter wheat farmers in the United States Central Great Plains currently practicing CT could improve the efficiency of the surface-applied fertilizer N and farm profitability by adopting NT.